2012
DOI: 10.1371/journal.pntd.0001644
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Nitric Oxide Synthase in Heart Tissue and Nitric Oxide in Serum of Trypanosoma cruzi-Infected Rhesus Monkeys: Association with Heart Injury

Abstract: BackgroundThe factors contributing to chronic Chagas' heart disease remain unknown. High nitric oxide (NO) levels have been shown to be associated with cardiomyopathy severity in patients. Further, NO produced via inducible nitric oxide synthase (iNOS/NOS2) is proposed to play a role in Trypanosoma cruzi control. However, the participation of iNOS/NOS2 and NO in T. cruzi control and heart injury has been questioned. Here, using chronically infected rhesus monkeys and iNOS/NOS2-deficient (Nos2 −/−) mice we expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 40 publications
4
61
0
1
Order By: Relevance
“…Moreover, this model of chronic CD recapitulated ECG abnormalities and cardiac tissue injuries [18] found in chagasic patients [6] and non-human primates [23]. Similarly to CD patients [15], high TNF levels are detected in the serum of chronically Colombian-infected C57BL/6 mice paralleling CCC [18, 21, 25].…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, this model of chronic CD recapitulated ECG abnormalities and cardiac tissue injuries [18] found in chagasic patients [6] and non-human primates [23]. Similarly to CD patients [15], high TNF levels are detected in the serum of chronically Colombian-infected C57BL/6 mice paralleling CCC [18, 21, 25].…”
Section: Discussionmentioning
confidence: 90%
“…The same study described a reduction of Cx43 protein levels in whole brains of T. cruzi-infected mice [47]. In monkeys, T. cruzi infection causes significant Cx43 loss in the cardiac tissue [51]. Clinical studies described that samples from chagasic patients showed alterations of cardiac Cx levels [52].…”
Section: Protein Expression Alterationsmentioning
confidence: 95%
“…Trypanosoma cruzi Cardiomyocytes Downregulated [43] Astrocytes Downregulated [44] Leptomeningeal cells Downregulated [44] Cardiomyocytes Downregulated [48] Cardiomyocytes Downregulated [51] Cardiomyocytes and heart human biopsies Downregulated [50] Toxoplasma gondii Astrocytes Downregulated [44] Leptomeningeal cells Downregulated [44] Cx26 Toxoplasma gondii Astrocytes Downregulated [44] Cx37…”
Section: Cx43mentioning
confidence: 99%
“…Here, we provide an overview of the mechanisms by which clinically important parasites -such as Schistosoma mansoni and S. japonicum, and hydatid cysts from Echinococcus multilocularis that localize primarily in the liverdrive liver fibrogenesis following their interaction with myeloid cell subsets. Other parasites, such as Trypanosoma cruzi , Taenia solium, Nippostrongylus brasiliensis and Schistosoma haematobium, inducing fibrosis in the heart, brain, lungs and bladder, respectively [9][10][11][12][13][14][15], and liver flukes, such as Clonorchis sinensis and Opisthorchis viverrini , causing bile periductal fibrosis, which increases the risk for cholangiocarcinoma [16][17][18][19][20], are not covered here, due to the marginal information on the phenotype, function and activation status of myeloid cells in these pathogenic processes.…”
Section: Introductionmentioning
confidence: 99%